(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY To describe the characteristics of cases presenting at the emergency department due to (suspected) poisoning for which consultation on patient management with the national Poisons Information Centre was required. METHODS Retrospective study at the emergency department of Bern University Hospital, Switzerland, from May 2012 to December 2017. Cases were identified in the electronic patient database using appropriate full-text search terms. Cases were excluded if the contact with the National Poisons Information Centre was through an external hospital or directly by the patient. Cases in which the poison centre was not contacted and cases without the patient’s general consent to use their medical data for research purposes were also excluded. RESULTS Overall, 667 cases from the study period were included. The median age was 32 years (range 16–94); 405 patients (61%) were female and 262 (39%) male. In most cases, the poisoning was acute (n = 631, 95%) and intentional (n = 505, 76%). The most common route of exposure was ingestion (n = 587, 88%) and the most commonly involved substances were sedatives (n = 185, 28%), antidepressants (n = 162, 24%) and non-opioid analgesics (n = 161, 24%). Impaired consciousness was documented in 299 cases (45%). Approximately half of the cases (n = 359, 54%) were of minor severity as assessed using the Poisoning Severity Score, 142 (21%) were of moderate severity, 110 (16%) were asymptomatic and 56 (8%) were severe. There were no fatalities. In most cases (n = 599, 90%), immediate therapeutic or diagnostic measures were undertaken prior to contact with the poison centre. Decontamination measures and specific antidotes undertaken or administered only after contacting the poison centre included whole bowel irrigation, haemodialysis, fomepizole, biperiden, silibinin, deferoxamine, leucovorin, dimercaptopropanesulfonic acid and hydroxocobalamin. Administration of a specific antidote/therapeutic agent was recommended in 87 cases (13%). In 70 of these 87 cases (80%), the specific agents were administered as recommended by the poison centre. In 17 cases (20%), the specific antidotes were not administered as recommended because of either clinical improvement (n = 11), termination of therapy based on laboratory results (n = 3), therapy refused by the patient (n = 2), or identification of a mushroom as non-poisonous (n = 1). In 109 cases (16%), there was no change in patient management after contacting the poison centre. CONCLUSIONS For patients presenting at the emergency department with severe poisoning, contact with the poison information centre can help to implement specific treatment and avoid fatalities. In less severe cases involving more common agents (e.g. paracetamol, benzodiazepines), contact can help to avoid unnecessary treatment and serve as a source of information and/or confirmation.